ETIKA DAKWAH USTADZ HANAN ATTAKI DALAM CHANNEL YOUTUBE @HANAN ATTAKI - Imulia Rahmadani Aziz (ADISAM PUBLISHER, 2023)
In today's era, social media has become one of the platforms for delivering religious teachings to the public. One of the preachers who utilizes social media for this purpose is Ustadz Hanan Attaki. He conducts his preaching through YouTube, where he shares his religious lectures. Ustadz Hanan is a young preacher widely recognized and admired by the youth due to his gentle speaking style and discussions that relate to their everyday lives. This research focuses on the ethical aspects of Ustadz Hanan Attaki's preaching in his video titled